Evaluación de los consumos de energía en el sistema de inyección de agua en el yacimiento M1 en el campo Edén Yuturi, bloque 12 operado por Petroamazonas EP, en el año 2015. Diseño de un sistema de recuperación secundaria energéticamente eficiente. - Fassler Carvajal, Ricardo Enrique (2016)
At the present research we start from an analysis of the operation of the pumping system for injection of formation water in the wells of the reservoir M1 in the field Eden Yuturi, block 12, in order to improve the oil recovery factor. The water properties analysis is done, which shows a good compatibility with the water reservoir is made. Through the techniques of total management of energy efficiency, it is shown that the pumps are classified as a vital element in the strategic decision to energy saving, determined by the distribution of Pareto that these make up 26,1 % of the installed power; It shows that pumps operating in parallel have poor performance, of 30 %, this being the cause of the low system efficiency. A methodology for the assessment of pumping systems for injection into the secondary recovery process based on technical and economic criteria is proposed. This methodology shows that the internal pressure of lower reservoir 810 m, it is not feasible to continue with the process of secondary recovery by itself, for which the operating cost is 83% of full cost. The proposed work is concluded with conceptual design for efficient injection system, with a performance of 76 % design; the value of savings energy efficiency of the proposed system reaches the amount of 112, 6 $/h.